Influence of leaf extracts and total flavonoids of Rhus tripartita (Ucria) Grande on phytobeneficial bacteria associated with its rhizosphere - Benaissa, Asmaa (Algerian Journal of Biosciences, 2021)
The article deals with the antimicrobial effect of Rhus tripartita (Ucria) Grande leaf extracts and total flavonoids against twelve antagonists Plant Growth Promoting Rhizobacteria of its rhizosphere, characterized in a previous study. The aim of this study is to demonstrate that leaves through their decomposition in the soil, may affect the distribution of bacterial communities in the rhizosphere. Leaves extracts were performed with distilled water, alcohol, methanol, hexane and chloroform as solvent and diluted in concentrations of 0.001, 0.01 and 0.1 mg/mL. The extraction of total flavonoids was carried out from leaves’ methanolic extract. The antimicrobial effect of the extracts was evaluated by the agar diffusion method and the determination of the minimum inhibitory concentration was carried out on a liquid medium. Alcohol, chloroform and methanol extracts were found to be the most effective on tested strains. The maximum zone inhibition was 18 mm, and the minimum zone inhibition was 7 mm. Rt 1: Bacillus licheniformis appears to be the most sensitive to all extracts. In contrast, Rt 7: Bacillus megaterium, seems to be the less sensitive strain. On the other hand, total flavonoids had a significant effect on 25% of the strains tested, mainly Bacillus genus. With a broad antimicrobial spectrum, the Rhus tripartita leaf extracts can be considered as a control agent for the distribution of the bacterial community in the rhizosphere. Therefore, our work showed that the plant could influence the bacterial diversity of its rhizosphere through its leaves.